2008
DOI: 10.1158/1078-0432.ccr-07-2052
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Tumor Heterogeneity Analysis in Early Rectal Cancer

Abstract: Purpose: Adequate preoperative staging of large sessile rectal tumors requires identifying adenomas that already contain an invasive focus, specifically those that are growing in or beyond the submucosa. We systematically compared chromosomal instability patterns in adenoma and carcinoma fractions of the same lesion to assess specific steps in rectal tumor progression. Experimental Design: We analyzed 36 formalin-fixed, paraffin-embedded tumors. Both the adenoma and carcinoma fractions were typed with single n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
1
38
0
1
Order By: Relevance
“…On the basis of the literature and our work, a frequency of 30-50% has been reported for 20q gain in sporadic CRC. 27,36 Although Abdel-Rahman et al reported only 54% of 20q gain in MMR-proficient familial CRC, this was found in almost all tumors that showed abnormalities. 35 When compared with the 20q gain frequency in a series of sporadic rectal carcinomas (36%), which was previously analyzed using the same methodology, we found that the frequency of 20q gain is significantly higher in MMR-proficient familial CRC (p ÂŒ 3.4  10 À3 ) as compared with the rectal cancers, which rarely show MMR-deficiency.…”
Section: Gain Of Chromosome 20qmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the literature and our work, a frequency of 30-50% has been reported for 20q gain in sporadic CRC. 27,36 Although Abdel-Rahman et al reported only 54% of 20q gain in MMR-proficient familial CRC, this was found in almost all tumors that showed abnormalities. 35 When compared with the 20q gain frequency in a series of sporadic rectal carcinomas (36%), which was previously analyzed using the same methodology, we found that the frequency of 20q gain is significantly higher in MMR-proficient familial CRC (p ÂŒ 3.4  10 À3 ) as compared with the rectal cancers, which rarely show MMR-deficiency.…”
Section: Gain Of Chromosome 20qmentioning
confidence: 99%
“…The observed aberrations that were most frequent in the MMR-proficient familial CRCs are well-known CRC aberrations, which are typically observed in sporadic CRCs. 27,36 We compared the profile of aberrations in our MMR-proficient familial CRCs series to that of sporadic CRC, MAP carcinomas and Lynch carcinomas series that we analyzed previously, using the same methodology. 17,19,26,27 The frequencies of gains at 8q and 13q, physical losses at 17p and chromosome 18 and cnLOH at 5q are similar in MMR-proficient familial CRC and sporadic CRC (Table S2).…”
Section: Snp Array Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis, we used a novel algorithm, lesser allele intensity ratio (LAIR), which is incorporated in beadarraySNP (5 (28), and can be useful in preoperative molecular staging of rectal cancer (29).…”
Section: Introductionmentioning
confidence: 99%
“…35 A subset of 60 tumors (14 FF and 46 FFPE) was used to determine the sensitivity and specificity of the assay on FF and FFPE tissue. The tumor cell percentage in the series was 50 to 80%.…”
Section: Samplesmentioning
confidence: 99%